Zirconium oxide film deposition properties to build transparent electronic devices in conjunction with tin dioxide - Fonseca, Lucas P. [UNESP]; Scalvi, Luis V.A. [UNESP] (My University, 2022)
ZrO2 thin films are deposited by the sol-gel dip-coating technique where the thermal annealing temperature and the number of deposited layers determine the properties of this material concerning the application in field-effect transistor (FET) devices in conjunction with SnO2 layer, also produced by sol-gel dip-coating. The best annealing temperature for the ZrO2 film was found as 400°C, along with a small number of layers and the position of the layer inside the oven, which determines the dominant heat transport mechanism of conduction or convection phenomena. The electrical insulating property of ZrO2 layers was confirmed with the current in the order of pA, even for layers about 100 nm thick. The temperature of 400°C also leads to a lower leak current through the gate in the device, which is three orders of magnitude lower than the source-drain current (in the order of a tenth of μA).
Keywords: thermal annealing; tin dioxide; transparent field-effect transistor; Zirconium oxide